POLÍTICAS PÚBLICAS DE INCLUSÃO ESCOLAR EM AÇÃO: UMA JORNADA COMPARADA ENTRE BRASIL E ITÁLIA - Venturini, Renata Santos (2020)
Our journey was driven by the desire to highlight the relevance of freedom of thought, to fight for democracy and to guarantee the rights of Special Education targeting students. We started our journey with the objective of understanding the process of ma